Fatigue failure simulation of a double-lap composites-metal bolted joint structure. Issue 1 (2nd January 2023) - Hou, Chi; Qiao, Jing; Wang, Wenzhi; Zhang, Chao
Abstract: The fatigue damage behavior and the failure characteristics of the T300/QY8911 laminate and 7050-T7451 aluminum single-bolt bolted joints were investigated by test and progressive damage analysis (PDA) in this article. The manufactured composites-to-metal bolted joints (CMBJs) with different thickness metal plates and lap-patterns have been tested in static and fatigue load case and the failure characteristics are compared. A modified Lemaitre fatigue damage model and a phenomenological composite fatigue damage model were proposed and applied simultaneously to capture the damage evolution in the laminate and the metal parts. The competition of the fatigue damage of the laminate and the metal parts in affecting the joint stiffness and the coupling of the damage accumulation were studied by PDA, and the results indicates that: the failing sequence of the CMBJs constructive parts may change between the static load case and the fatigue load case; the fatigue damage of the metal parts has little effect on the joint stiffness of the CMBJs, nevertheless, there is certain coupling of the laminates fatigue damage and metal fatigue damage in the CMBJs, the harden or soften of the metal parts by fatigue hardening or crack progression would promote or slow down the damage accumulation in laminate.